TEENAGE SPEECH ERRORS: A PSYCHOLINGUISTIC STUDY OF RILEY'S UTTERANCES IN 'INSIDE OUT 2' - Veronika Theodora Male; Rusfandi Rusfandi; Ayu Liskinasih (UIN Raden Mas Said Surakarta, 2025)
One aspect illustrating the connection between language and its psychological functions is speech production, which can reveal how psychological, cognitive, and physical conditions influence spoken language, potentially leading to speech production problems. This study investigates speech production issues in a fictional setting through the expressions of Riley, a character in the movie Inside Out 2, who faces emotional and cognitive challenges during adolescence. The aim of this analysis is to identify the variety of speech production errors and the underlying reasons for these errors in Riley's utterances. Using qualitative content analysis, the research applies Levelt’s (1989) speech production model, Warren’s (2013) theory of speech errors, and Clark and Clark’s (1977) framework to identify and categorize speech errors in Riley’s speech. Data were collected by documentation through watching Inside Out 2, transcribing Riley's utterances, identifying errors, and categorizing them by type, stage, and cause based on established theoretical frameworks. Eight types of errors were found i.e.: silent pauses, filled pauses, stuttering, repetition, substitution, anticipation, omission, and self-repair. The most common error is the silent pause, while substitution, anticipation, and repetition occur less frequently. Most errors are influenced by psychological factors, such as anxiety and emotional instability related to puberty, alongside cognitive and motor constraints. The findings demonstrate how emotional and cognitive challenges affect speech production in teenagers, highlighting the relevance of psycholinguistic theory in analyzing natural speech within fictional narratives.